2020
DOI: 10.1126/scisignal.aav1256
|View full text |Cite
|
Sign up to set email alerts
|

The parkin-coregulated gene product PACRG promotes TNF signaling by stabilizing LUBAC

Abstract: The Parkin-coregulated gene (PACRG), which encodes a protein of unknown function, shares a bidirectional promoter with Parkin (PRKN), which encodes an E3 ubiquitin ligase. Because PRKN is important in mitochondrial quality control and protection against stress, we tested whether PACRG also affected these pathways in various cultured human cell lines and in mouse embryonic fibroblasts. PACRG did not play a role in mitophagy but did play a role in tumor necrosis factor (TNF) signaling. Similarly to Parkin, PACRG… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 89 publications
0
18
0
Order By: Relevance
“…Interestingly, the HOIP UBA does not bind ubiquitin [ 27 ], but instead interacts with ubiquitin-like (UBL) domains from other LUBAC subunits HOIL-1L and SHARPIN, which release autoinhibition of HOIP [ 51–54 ]. Recently the parkin coregulated gene (PACRG) product was identified as a novel LUBAC component, which interacts with LUBAC via the HOIP UBA and can functionally compensate for loss of SHARPIN from the complex [ 55 ]. As PACRG does not have a UBL, it is unclear how this interaction occurs, and whether PACRG represents an additional LUBAC component or replaces one of the cofactors HOIL-1L or SHARPIN in specific sub-complexes.…”
Section: Ancillary Ubiquitin Binding Domainsmentioning
confidence: 99%
“…Interestingly, the HOIP UBA does not bind ubiquitin [ 27 ], but instead interacts with ubiquitin-like (UBL) domains from other LUBAC subunits HOIL-1L and SHARPIN, which release autoinhibition of HOIP [ 51–54 ]. Recently the parkin coregulated gene (PACRG) product was identified as a novel LUBAC component, which interacts with LUBAC via the HOIP UBA and can functionally compensate for loss of SHARPIN from the complex [ 55 ]. As PACRG does not have a UBL, it is unclear how this interaction occurs, and whether PACRG represents an additional LUBAC component or replaces one of the cofactors HOIL-1L or SHARPIN in specific sub-complexes.…”
Section: Ancillary Ubiquitin Binding Domainsmentioning
confidence: 99%
“…The PACRG gene encodes a protein that forms a large molecular complex with chaperones. It has recently been described that the PACRG protein plays an important role in tumor necrosis factor (TNF) signaling, and this function of PACRG in positively regulating TNF signaling may help to explain the association of PACRG polymorphisms with increased susceptibility to intracellular pathogens [45]. Agirre et al [46] studied the role of promoter hypermethylation in the regulation of PACRG expression in different tumour cell lines and primary patient samples and demonstrated that abnormal methylation resulted in downregulation of PACRG gene expression.…”
Section: Discussionmentioning
confidence: 99%
“…In C. elegans PACRG mutants have reduced insulin signaling. Also, PCARG plays a key role in the regulation of mitophagy (Stephenson et al 2018 ) and ubiquitynylation (Loucks et al 2016 ), its knockout leads to defective NFκB signaling (Meschede et al 2020 ) and CHOP upregulation (Han et al 2017 ), which in adipose tissue result in increased proinflammatory macrophage polarization (M1) and insulin resistance (Suzuki et al 2017 ). Thus, we note that PACRG is also involved in ER stress.…”
Section: Discussionmentioning
confidence: 99%